Pengaruh Model Pembelajaran Kooperatif Course Review Horay Bermuatan Literasi Sains Pada Materi Sistem Reproduksi Manusia Di SMAN 4 Pariaman - Khairunnisa Khairunnisa; syamsurizal syamsuizal; Relsas Yogica; Ganda Selaras (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Research on the problems that exist in Pariaman 4 Senior High School, student learning competencies are still low. The effort that can be done is to apply the cooperative learning model course review horay  type with literacy content of SMAN 4 Pariaman. The purpose of this study was to study student learning through a cooperative model of course review horay  type with literacy at SMAN 4 Pariaman. This type of research is experimental research with randomized posttest control group design. The population in this study were all students of class XI IPA SMAN 4 Pariaman registered in 2018/2019. Sampling was done using the Simple cluster Sampling technique, which was chosen as the research sample was class XI IPA.1 as the experimental class and XI IPA.3 as the control class. The instrument used consisted of posttest questions for knowledge competencies, observation sheets for competencies and skills. The assessment hypothesis using the t-test, can prove the knowledge competency tcount 4.13> ttable 1.67, competency assessment value 80% with good categories and competency skills value tcount 3.21> ttable 1.67. This is an accepted hypothesis. It was concluded that the cooperative model of course review horay type with literacy opposed the competence of knowledge, attitudes, and skills of class XI IPA students of SMAN 4 Pariaman.